A Uterus‐Inspired Niche Drives Blastocyst Development to the Early Organogenesis. Issue 28 (17th July 2022) - Gu, Zhen; Guo, Jia; Zhai, Jinglei; Feng, Guihai; Wang, Xianning; Gao, Zili; Li, Kai; Ji, Shen; Wang, Leyun; Xu, Yanhong; Chen, Xi; Wang, Yiming; et al.
Abstract: The fundamental physical features such as the mechanical properties and microstructures of the uterus need to be considered when building in vitro culture platforms to mimic the uterus for embryo implantation and further development but have long been neglected. Here, a uterus‐inspired niche (UN) constructed by grafting collagen gels onto polydimethylsiloxane based on a systematic investigation of a series of parameters (varying concentrations and thicknesses of collagen gel) is established to intrinsically specify and simulate the mechanics and microstructures of the mouse uterus. This brand‐new and unique system is robust in supporting embryo invasion, as evidenced by the special interaction between the embryos and the UN system and successfully promoting E3.5 embryo development into the early organogenesis stage. This platform serves as a powerful tool for developmental biology and tissue engineering. Abstract : A uterus‐inspired niche drives blastocyst development to early organogenesis. The uterine horn's modulus and the endometrium microstructure is mimicked to construct a uterus‐inspired niche to support the embryo development to the early organogenesis stage in vitro and to study the invasion of the embryo into collagen fibers for in‐depth studies of embryonic implantation in the future.